2020
DOI: 10.1038/s41598-020-65605-w
|View full text |Cite
|
Sign up to set email alerts
|

Hyperuricemia is associated with metabolic syndrome in the community very elderly in Chengdu

Abstract: Hyperuricemia is a risk factor for cardiovascular metabolic diseases. However, in the very elderly, the relationship between hyperuricemia and the metabolic syndrome (MetS) is not yet clear. This study was aimed to investigate the potential association between hyperuricemia and MetS in community very elderly in Chengdu. In this cross-sectional study, 1056 very elderly in the community were enrolled. Serum uric acid (SUA), fast plasma glucose, triglycerides and high–density lipoprotein cholesterol were measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…The association between hyperuricemia and MetS has been explored in many cross-sectional studies, but prospective studies are rare ( 7 9 , 19 , 20 ). Some studies suggest that MetS can increase the incidence of hyperuricemia ( 19 21 ); however, others suggest that hyperuricemia should be included as a component of MetS ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The association between hyperuricemia and MetS has been explored in many cross-sectional studies, but prospective studies are rare ( 7 9 , 19 , 20 ). Some studies suggest that MetS can increase the incidence of hyperuricemia ( 19 21 ); however, others suggest that hyperuricemia should be included as a component of MetS ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…Both hyperuricemia and MetS are common chronic diseases, and studies have indicated that hyperuricemia and MetS are closely related ( 7 9 ). A cross-sectional study indicated that hyperuricemia was an important factor in MetS, but it was not discussed individually in men and women ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The complications of obesity, such as hyperglycemia and hyperlipidemia, were also indicated by the clinical variables at the end of this study. An epidemiological cross-sectional study on patients with diabetes and obesity reported that serum UA level was significantly associated with obesity and BMI [39] and positively correlated with metabolic syndrome [40]. Moreover, individuals with obesity can also develop chronic kidney disease due to insulin resistance and hypertension, along with systemic inflammation and dyslipidemia.…”
Section: Discussionmentioning
confidence: 99%
“…It is a real public health problem around the world, with a frequency and a prevalence increasing in both developing and developed countries (ViswanathanI and Deepa, 2006). Serum uric acid (SUA) is the end product of purine metabolism in humans and many studies have reported the association between hyperuricemia and the various components of the MS, in particular obesity, blood pressure, hyperlipidemia as well as glucose intolerance (Ames et al, 1981;Wilson et al, 2005;Lorenzo et al, 2007;Fabbrini et al, 2014;Zhang et al, 2016;Cheserek et al, 2018;Huang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%